Pengaruh Investasi Dan Tenaga Kerja Terhadap Pertumbuhan Ekonomi Di Kota Makassar - Andi Aenatul Mawadda; Asriati, Asriati; Muhammad Rusydi (Jurnal Publikasi Ekonomi dan Akuntansi, 2025)
This study aims to determine the influence of investment and labor on economic growth in Makassar City. The method used is a quantitative approach with multiple linear analysis, using secondary data from 2014-2023. The results of this study show that investment has a positive and significant effect on economic growth, the greater the investment in a country, the higher the level of economic growth that can be achieved, and the labor force has a negative and insignificant effect, this is because the quality of labor is very low in economic growth.